i-LENUK: Sistem Pendataan Penyu Berbasis Aplikasi Bagi Pokmaswas Pantai Taman Kili Kili, Trenggalek, Jawa Timur - Ahmad Kurniawan; Neneng Nurlaila; Arief Darmawan; Muhammad Zaini Rahman; Azizah Nurul Asri; Abdullah Harits (Journal of Innovation and Applied Technology, 2020)
Taman Kili Kili Beach is a nesting place for turtles. There are Olive Ridley (Lepidochelys olivacea), Hawksbill Turtle (Deretmocelys imbricate), Green Turtle (Chelonian mydas) and Leatherback (Dermocelys oliacea) that found completing their natal homing to this area during the night. The beach area was conserved and managed by a group of local community that called as Pokmaswas Taman Kili-Kili Beach with consideration of the government at the village level. However, due to limitation of Pokmaswas human resources, turtle data tabulation process still conducted by filling sheet manually and it went ineffective and prone to lost. i-LENUK, an application-based on android that developed for turtle data tabulation and database system for the Pokmaswas of Taman Kili Kili introduced and applied to solved and increase effectiveness. Pokmaswas members have been trained as tabulator and administrator in the turtle data tabulation including verification and maintain data as well.